Chrysanthemum-like TiO2 nanostructures with exceptional reversible capacity and high coulombic efficiency for lithium storage1. Issue 12 (28th March 2015) - Wang, Lin; Nie, Zhongyuan; Cao, Chuanbao; Zhu, Youqi; Khalid, Syed
<x xml:space="preserve">Abstract</x> Rational chrysanthemum-like TiO2 nanostructures have been developed by a facile effective approach as the anode materials, exhibiting good lithium storage performances with excellent rate capacity and good cycling stability (see the picture), which are much better than those of TiO2 electrodes reported so far under similar testing conditions.